Chelsea shows her work in finding the solution to 4x-5=2+3(x-3). After checking her answer in the original equation, she found that it did not work. Where did she make a mistake?

Respuesta :

Answer: x = -2, it could be they didnt follow the right order of mathematic operation (BODMAS)

Step-by-step explanation:

4x-5 = 2+3(x-3)

following the order of operation we must open the bracket first

4x - 5 = 2 + 3x - 9

4x - 5 = 3x - 7

we now collect like terms

4x - 3x = -7 + 5

x= -2

Now checking the answer in the original equation, we will just put -2 wherever x is.

4x - 5 = 2 + 3(x-3)

4(-2) - 5 = 2 + 3( -2 -3)

We will have to deal with the bracket first before we proceed;

-8-5 = 2 + 3(-5)

-13 = 2 - 15

-13 = -13

Answer:

she subtracted 5 instead of adding 5

Step-by-step explanation:

i did this on ttm and got it right